Potential impacts of Hematodinium perezi on the male reproductive system of Portunus segnis from the Great Bitter Lake, Egypt - Rady, Ahmed; Abu Jabel, Omyma (Journal of King Abdulaziz University: Marine Sciences, 2023)
From October 2020 to September 2021, researchers examined various facets of the reproductive biology of male Portunus segnis crabs caught in the fishing port of the Great Bitter Lakes on Egypt’s Suez Canal coast. The male reproductive system of Portunus segnis consists of two testes, a commissure, two vas deferentia, and two ejaculatory ducts internally. It is bilaterally symmetrical and creamy to whitish in appearance. The three components of Vas deferentia were the Anterior (AVD), Median (MVD), and Posterior (PVD). There are three stages of male gonad development: immature, maturing, and mature. For light microscopic examinations, tissues from the testis, anterior vas deferens (AVD), median vas deferens (MVD), posterior vas deferens (PVD), and ejaculatory duct were fixed in Bouin’s solution. The blue swimming crab Portunus segnis is an important host of parasitic dinoflagellates from the genus Hematodinium. The blue swimming crab Portunus segnis’s commercial supplies have been harmed by outbreaks of these parasites. Hematodinium perezi, a dinoflagellate, had no discernible impact on the gonad growth and development of its host Portunus segnis. For uninfected and infected males, the size at first sexual maturity was estimated to be 66.3 and 67.3 mm carapace width, respectively.